2015
DOI: 10.1177/0018720815591905
|View full text |Cite
|
Sign up to set email alerts
|

Does Using a Chair Backrest or Reducing Seated Hip Flexion Influence Trunk Muscle Activity and Discomfort? A Systematic Review

Abstract: Objective: This paper systematically reviews the effect of chair backrests and reducing seated hip flexion on low back discomfort (LBD) and trunk muscle activation.Background: Prolonged sitting commonly exacerbates low back pain (LBP). Several modifications to seated posture and chair design have been recommended, including using chairs with backrests and chairs that reduce hip flexion.Method: Electronic databases were searched by two independent assessors. Part 1 of this review includes 26 studies comparing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 83 publications
1
16
0
1
Order By: Relevance
“…Chairs that put an individual in a semi-kneeling position have been shown to increase pedal cutaneous blood flow in subjects over traditional chairs, though participants of that study indicated they preferred to sit in traditional chairs (15). Further, sitting in chairs with backrests have been found to reduce paraspinal muscle activation, not necessarily reduce low back pain (16). More recently, radiographic evidence has supported the idea that using a chair with back support, can minimize changes to lumbar lordosis and pelvic parameters that occur between sitting and standing (17), but this study did not assess the results of using a kneeling chair.…”
Section: Discussionmentioning
confidence: 78%
“…Chairs that put an individual in a semi-kneeling position have been shown to increase pedal cutaneous blood flow in subjects over traditional chairs, though participants of that study indicated they preferred to sit in traditional chairs (15). Further, sitting in chairs with backrests have been found to reduce paraspinal muscle activation, not necessarily reduce low back pain (16). More recently, radiographic evidence has supported the idea that using a chair with back support, can minimize changes to lumbar lordosis and pelvic parameters that occur between sitting and standing (17), but this study did not assess the results of using a kneeling chair.…”
Section: Discussionmentioning
confidence: 78%
“…However, the trunk and lower limbs are involved in a variety of motor activities such as reaching, sitting without support, and active mobilization exercises [31, 32]. Therefore, a useful task has to be performed by the control group without incorporating the trunk or lower limbs.…”
Section: Methods and Designmentioning
confidence: 99%
“…The dental stool has an influence on such posture [11][12][13], because it induces the use of certain postural patterns to find a more comfortable and/or functional position [11][12][13]. In addition, the curvature of the spine, as well as the location and correct position of the head and pelvis are crucial for the biomechanics of the sitting position [14][15][16].…”
Section: Introductionmentioning
confidence: 99%